Greenland’s lithospheric structure and its implications for geothermal heat flow - Wansing, Agnes Dakota (Christian-Albrechts-Universität zu Kiel, 2024)
In light of the contribution of the Greenland ice sheet to sea-level rise, the geothermal heat flow (GHF) and lithospheric structure of Earth’s largest island are of great interest. While extensively studied, both are ill-constrained. Therefore, I evaluated the lithospheric structure and GHF in Greenland by focusing on data integration and model consistency. First, a new GHF map is predicted in a machine-learning framework, trained on global GHF measurements and a multitude of globally available geophysical datasets. No evidence for plume-lithosphere interaction in the form of elevated GHF can be found along the Iceland hotspot track. In the next step, a full lithospheric model based on the integration of multiple data sets, is constructed. The model’s lithospheric mantle and its boundaries are adjusted to fit satellite gravity gradient and seismic tomography data. The crustal density and susceptibility structure is determined by a joint inversion of gravity and magnetic data. The model self-consistently reproduces gravity, topographic, and magnetic data and seismic velocities from a tomography model. To compare the modelled crustal parameters with in-situ data, a Greenland-specific petrophysical database was established and evaluated statistically. Finally, a regional model for the upper crust in South Greenland is derived from joint inversion of potential field data. The employment of a new, high-resolution magnetic data set allows the compilation of a simplified geological map. By sampling radiogenic heat production (RHP) data onto the geology polygons, a model for sub-ice RHP and the resulting GHF is proposed. The presented results demonstrate the importance of lithospheric modelling and GHF estimation coupling. It is necessary to consider the two main contributions to GHF, the thermal field of the mantle lithosphere and heat production in the crust on their respective length scales.